Molecular diagnosis of Chinese patients with 21-hydroxylase deficiency and analysis of genotype–phenotype correlations. (April 2017) - Zhang, Bo; Lu, Lin; Lu, Zhaolin
Objective: The spectrum of molecular defects in Chinese patients with 21-hydroxylase deficiency (21-OHD), and genotype–phenotype relationships are unknown. Methods: We screened eight patients with non-classical (NC) 21-OHD and 35 with classical 21-OHD, and detected nine known mutations. Results: The most frequent mutation among the 43 21-OHD cases was p.Ile172Asn (allele frequency, 36.0%), followed by c.290-13A/C > G (20.9%), Del (8.6%), p.Pro30Leu (7.0%), p.Gln318Ter (7.0%), p.Val281Leu (4.7%), p.Arg356Trp (2.3%), p.[Ile236Asn; Val237Glu; Met239Lys] (2.3%), and E3Δ8 bp (1.2%). The frequency spectrum of CYP21A2 mutations in the Chinese population was similar to that in the Japanese population, except that p.Val281Leu was identified in Chinese NC21-OHD patients at a frequency of 25.0%, whereas it was absent in Japanese patients. We found that genotype could predict phenotype in 88.3% of patients. Conclusion: Some characteristics appear to be unique to the Chinese population, but genotype was strongly predictive of phenotype.